High-quality chronic care delivery improves experiences of chronically ill patients receiving care - Cramm, Jane Murray (Oxford University Press, 2013)
OBJECTIVE: Investigate whether high-quality chronic care delivery improved the experiences of patients. DESIGN: This study had a longitudinal design. SETTING AND PARTICIPANTS: We surveyed professionals and patients in 17 disease management programs targeting patients with cardiovascular diseases, chronic obstructive pulmonary disease, heart failure, stroke, comorbidity and eating disorders. MAIN OUTCOME MEASURES: Patients completed questionnaires including the Patient Assessment of Chronic Illness Care (PACIC) [T1 (2010), 2637/4576 (58%); T2 (2011), 2314/4330 (53%)]. Professionals' Assessment of Chronic Illness Care (ACIC) scores [T1, 150/274 (55%); T2, 225/325 (68%)] were used as a context variable for care delivery. We used two-tailed, paired t-tests to investigate improvements in chronic illness care quality and patients' experiences with chronic care delivery. We employed multilevel analyses to investigate the predictive role of chronic care delivery quality in improving patients' experiences with care delivery. RESULTS: Overall, care quality and patients' experiences with chronic illness care delivery significantly improved. PACIC scores improved significantly from 2.89 at T1 to 2.96 at T2 and ACIC-S scores improved significantly from 6.83 at T1 to 7.18 at T2. After adjusting for patients' experiences with care delivery at T1, age, educational level, marital status, gender and mental and physical quality of life, analyses showed that the quality of chronic care delivery at T1 (P < 0.001) and changes in care delivery quality (P < 0.001) predicted patients' experiences with chronic care delivery at T2. CONCLUSION: This research showed that care quality and changes therein predict more positive experiences of patients with various chronic conditions over time.